Physiology, transcriptomics, and metabolomics reveal the regulation of calcium distribution in tomato under reduced vapor pressure deficit and increased calcium fertilizer - Xuemei Yu; Luqi Niu; Yuxin Liu; Yuhui Zhang; Jianming Li; Shuhui Zhang (Horticultural Plant Journal, 2025)
High atmospheric vapor pressure deficit (VPD) reduces the calcium (Ca) distribution in tomato (Solanum lycopersicum L.) fruits, severely reducing fruit mass. Reducing the VPD or increasing Ca fertilizer is an important measure to improve Ca distribution in fruits. However, the mechanism through which VPD and Ca regulate fruit Ca distribution remains unclear. This study investigated the effects of high and low VPD and Ca levels on Ca distribution and fruit mass based on carbon fixation, water transport dynamics, and pectin and Ca content and identified key differential genes and metabolites through transcriptome and metabolome analyses. The results showed that both reducing VPD under low Ca and increasing Ca under high VPD increased water and Ca transport to fruits. The increased Ca combined with pectin to form Ca pectinate, which effectively stabilized the cell wall and enhanced the fruit mass. Reduced VPD under low Ca increased the distribution of Ca to fruits but decreased the distribution of Ca to leaves. Lower Ca distribution in leaves increased their absorption of other nutrients, such as potassium, magnesium, copper, and zinc, which increased the stomatal size and density, thereby improving plant carbon absorption and assimilation efficiency. However, transcriptomic and metabolomic data indicated that carbohydrates, as important regulatory factors under drought stress, increased significantly under high VPD, thereby reducing the fruit water potential while improving fruit water and Ca absorption. Therefore, the carbon assimilation efficiency, water transport capacity, and differential genes and metabolites regulated Ca distribution. This work provides a theoretical basis for environmental and fertilizer management in greenhouse tomato production.